Serology can help in the early diagnosis of leprosy in monitoring household contacts - Gabriela Tayrine CAETANO; Ludmila MOREIRA; Charles Scott FOREMAN; Lucas Henrique SAMPAIO (Universidade de Brasília, 2015)
Phenolic glycolipid antibody (PGL-I) is considered a relevant marker of leprosy. However anti PGL-I test is not been widely implemented in field situations. In this work we performed a study of examining the anti-PGL-I to HHC recruited in Anápolis, Brazil, endemic city for leprosy. They were performed three evaluations during this follow up. During this study a proportion of incident cases significantly higher (p